Solipsism, self-indulgence and circular arguments: Why autoethnography promises much more than it delivers - Freeman, John (Intellect, 2013)
The dominance of autoethnography has obscured a measured evaluation of the compatibility of autoethnographic research with its subject matter, and also of the research value of predominantly personal narratives – those stories by researchers who locate and regard themselves as the research subject and who then write evocative stories of their experiences. These are often the most difficult forms for autoethnography to accommodate, relying as they do on experience reading as its own analysis and diary-like description of the researcher/writer’s life standing for a retelling that provides an adequate informing of our understanding of a particular cultural context. It can be hard to distinguish these stories from autobiography. In these cases, autoethnography often appears to be used as little more than a relatively research-friendly term, as something that sounds more academically legitimate than autobiography but which has more in common with drawing the reader into the researcher’s own life than using one’s culturally located experiences as something that opens a door onto wider understanding.